If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5x(x-3)-7(6-x)+29=50-3(8-x)
We move all terms to the left:
5x(x-3)-7(6-x)+29-(50-3(8-x))=0
We add all the numbers together, and all the variables
5x(x-3)-7(-1x+6)-(50-3(-1x+8))+29=0
We multiply parentheses
5x^2-15x+7x-(50-3(-1x+8))-42+29=0
We calculate terms in parentheses: -(50-3(-1x+8)), so:We add all the numbers together, and all the variables
50-3(-1x+8)
determiningTheFunctionDomain -3(-1x+8)+50
We multiply parentheses
3x-24+50
We add all the numbers together, and all the variables
3x+26
Back to the equation:
-(3x+26)
5x^2-8x-(3x+26)-13=0
We get rid of parentheses
5x^2-8x-3x-26-13=0
We add all the numbers together, and all the variables
5x^2-11x-39=0
a = 5; b = -11; c = -39;
Δ = b2-4ac
Δ = -112-4·5·(-39)
Δ = 901
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-11)-\sqrt{901}}{2*5}=\frac{11-\sqrt{901}}{10} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-11)+\sqrt{901}}{2*5}=\frac{11+\sqrt{901}}{10} $
| 97x+1=98x | | 8+2x=-3/2x+1 | | p/24=250 | | 2-3x-5=15 | | -6+x/8=-13 | | 2.7k=-13.5 | | 45x+10=35x+30 | | (X+2)(x-4)=x^2+9 | | (3d)/(4)+5=11 | | 5(x-2)+7=22 | | -21-3m=-3(1-5m) | | −2(x+4)+14=15−3x | | 6(3x-2)=9(2x-1)+-3 | | 6(19)x=2,166 | | 7w+4+3w+11=77 | | -x+11x-16=74 | | 6(3x-2)=9(2x-1)+3 | | 6(3x-2)=9(2x-1)+3x | | 16q-4q-6q=12 | | (2x+1)(x+8)=180 | | 4(2x-6)=3(2x-4)+2x | | 3x/2+4=16 | | -y/7=-58 | | 8+.5x=14 | | y-1,564=1,256 | | x-8(3.16)=3.16 | | 19x-6=70 | | 2(8/7)x=64/7 | | 3^m=5^m | | -8+n=-(1-8n) | | 3(16)-2(4.5)=x | | 7x-1-6x=-5 |